A Model forSuccess of an International Joint Venture in India: Validated through Analytic Hierarchy Process - Kumar Pandey, Mayank; Singh, Dileep; Kaushik, Rohit; Vats, Ruchika (International Journal of Engineering and Technology, 2018)
Worldwide business pattern has opened innovative ways of agreements for those who want to take advantage of the fruits of free flow of resources beyond national boundaries. International joint venture (IJV) is one of several such strategic moves. This research targets at discovering various factors of international joint ventures as a strategic alliance, the requirement for such alliance and the consequences. Success of an IJV is driven by IJV partnersâ€™ ability to make collaboration by joining integral strengths. To examine the synergy created from various complementary strengths in the context of IJVs formed between established market firms and Indian firms in India. This is a conceptual paper where a universal model is proposed to show, how synergy can be created through complementary strengths of Indian company and foreign company in success of an IJV. This paper exhibits the use of analytic hierarchy process (AHP) and ranks the synergy. Further, it has been depicted that various strategies like increased competitiveness, deterring the global competitors, risks diversification, technology transfer, leveraging the financial regulations and customer value proposition can be adopted to derive high to low synergy.Â Â